The biomineralization of silica induced stress tolerance in plants: a case study for aluminum toxicity - Yingming Feng; Hongxiang Han; Wei Nong; Jiao Tang; Xingyun Chen; Xuewen Li; Lei Shi; Vladimir D. Kreslavski; Suleyman I. Allakhverdiev; Sergey Shabala; Weiming Shi; Min Yu (Plant Signaling & Behavior, 2023)
Biomineralization in plant roots refers to the process of cell-induced self-assembly to form nanostructures on the root surface. Silicon (Si) is the second most abundant element in soils, and beneficial to plant growth. Meanwhile, silicon is shown to participate in the process of biomineralization, which is useful for improving mechanical strength and alleviating biotic and abiotic stress, for example silicic acid polymerizes to form amorphous silica (SiO2–nH2O) in the process of growing to resist fungi and environmental stress. This process alters physical and chemical properties of cell wall. However, the mechanistic basis of this process remains unclear. Aluminum toxicity is a major constraint affecting plant performance in acid soil. This paper summarizes recent research advances in the field of plant biomineralization and describes the effects of silicon biomineralization on plant aluminum tolerance and its adaptive significance, using aluminum toxicity as a case study.